Faculty of Special Engineering - Polednak, Pavel (Communications - Scientific letters of the University of Zilina, 2003)
The Faculty of Special Engineering of the University of Žilina was transformed from the Military Faculty of the University of Žilina. The previous faculty was established in 1952 and, at this time the Faculty was constituted as the Railway Faculty and a part of the Military Technical University in Brno, the Czech Republic. In 1953 the Railway Faculty was relocated to the Railway University in Prague, the Czech Republic and renamed the Military Faculty. This Military Faculty was in 1959 transferred to Žilina and became a part of the newly established Technical University of Transport. Today’s name of the university is the University of Žilina. Under the authority of the Ministry of Transport, Posts and Telecommunications of the Slovak Republic, the Ministry of Education of the Slovak Republic, the Ministry of Defense of the Slovak Republic, the Accreditation Committee of the Government of the Slovak Republic and by acclamation of the Academic Senate of the University of Žilina, the Military Faculty was on 9th February 1998 renamed to the Faculty of Special Engineering of the University of Žilina.